Problems of Legal Regulation of Criminal Responsibility for Illegal Plunder and Circulation of Especially Valuable Strains of Cattle - M. V. Bavsun (Сибирское юридическое обозрение, 2014)
The article deals with the disputable issues in legal regulation of criminal responsibility for plunder and circulation of especially valuable strains of wild cattle, acting as a subject of legal and criminal protection, Art. 258.1 of the RF CC (Criminal Code of the Russian Federation). As a conclusion the author offers the variant of proposals for improvement of legislative construction of the norm considered on the ground of the analysis conducted.